Integral Type Contraction in Dislocated Metric Spaces - Goyal, A.K.; Gupta, Neelmani (International Journal of Membrane Science and Technology, 2023)
In this paper, by using the notion of compatibility, weak compatibility, occasionally weak compatibility and commutativity, we establish some common fixed point theorems for six mappings satisfying integral type contractive conditions in complete dislocated metric spaces. Our work improves and extends some earlier results in the literature.